2013
DOI: 10.4103/0974-7796.115732
|View full text |Cite
|
Sign up to set email alerts
|

Is periprostatic nerve block a gold standard in case of transrectal ultrasound-guided prostate biopsy?

Abstract: Introduction:Controversy exists over the pain during prostate biopsy. Periprostatic nerve block (PNB) is a gold standard anesthetic technique during transrectal ultrasound (TRUS)-guided prostate biopsy. Recent studies showed that PNB alone is insufficient as analgesic. We compared the efficacy of tramadol and intraprostatic nerve block (INB) in addition to PNB.Materials and Methods:We conducted a prospective double blinded placebo controlled study at our institute in 150 consecutive patients. Patients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(14 reference statements)
0
10
1
1
Order By: Relevance
“…Gill et al 26 reported on 234 patients undergoing the same TRUS TR procedure with the addition of a periprostatic nerve block, which is considered the gold standard for TRUS-guided prostate biopsy. 27 Of those patients who gave a pain score, only 21.9% of patients in total scored pain at 2 or higher and 75% patients scored pain as 1 or 0 (very mild or no pain), and the mean pain score was lower than that observed by Igdem et al at 1.1.…”
Section: Fiducial Marker Implantationcontrasting
confidence: 39%
“…Gill et al 26 reported on 234 patients undergoing the same TRUS TR procedure with the addition of a periprostatic nerve block, which is considered the gold standard for TRUS-guided prostate biopsy. 27 Of those patients who gave a pain score, only 21.9% of patients in total scored pain at 2 or higher and 75% patients scored pain as 1 or 0 (very mild or no pain), and the mean pain score was lower than that observed by Igdem et al at 1.1.…”
Section: Fiducial Marker Implantationcontrasting
confidence: 39%
“… 6 31 Eight articles compared IRLA with no anesthesia or placebo gel; 6 13 six articles compared PPNB with no anesthesia; 7 , 11 , 14 17 three articles compared PPNB with periprostatic placebo injection; 10 , 14 , 18 six articles compared PPNB with IRLA; 7 , 10 , 11 , 19 , 21 nine articles compared combined PPNB and IRLA with PPNB alone; 21 29 and four articles compared combined PPNB and IPNB with PPNB alone. 15 , 17 , 30 , 31 For studies comparing PPNB with periprostatic placebo injection, an equivalent volume of normal saline was used. In all studies, biopsies were operated with an 18 G needle, and six to 14 core biopsies were performed for the participants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, periurethral infiltration with local anesthetic before operation can also reduce immediate postoperative pain. 27,28 However, these approaches have not been introduced in the management of CRBD. Further studies in this area are warranted.…”
Section: Discussionmentioning
confidence: 99%